Differences in mental health outcomes between adolescent elite athletes and peers not engaged in elite sport - Gerber, M.; Kellmann, M.; Brand, S.; Gygax, B.; Ludyga, S.; Müller, C.; Ramseyer, S.; Jakowski, S. (Current Issues in Sport Science, 2022)
Elite athletes are confronted with various challenges, pressures and stressors. Due to their status as student and athlete, adolescent elite athletes are exposed to a double burden of stress (pressure to be simultaneously successful in school and elite sport), which adds to the general risk for psychological problems in this developmental period. To facilitate the combination of elite sport and education, almost all cantons in Switzerland have established schools, which offer a special track for adolescent elite athletes. We examine (i) whether adolescent elite athletes differ from controls in a series of mental health outcomes, (ii) whether links between perceived stress and mental health symptoms are particularly strong among adolescent elite athletes, and (iii) whether perceived stress and training/competitive load interact to explain variance in mental health. Cross-sectional data from 156 athletes (134 from sport classes, 22 from regular classes) and 150 non-athletic controls (peers not engaged in elite sport) were analysed. All students were recruited from Swiss Olympic Partner schools, and attended grade 10-14. In total, 5-19% of the students reported moderate-to-severe mental health symptoms. With regard to depressive, burnout and insomnia symptoms, no significant differences were found between athletes and controls. A consistent link was observed between higher stress perceptions and more frequent mental health symptoms. However, engaging in elite sport did not seem to be an additional source of distress (or vulnerability factor) among adolescents with moderate-to-high stress levels. High training/competitive load did not amplify the association between perceived stress and mental health symptoms in elite athletes. Currently, no comprehensive framework or model of care exists to support and respond to mental health needs of young elite athletes. Our findings show that it is time to address these challenges to prevent mental health issues and ensure that young athletes can flourish while developing their full potential.